Propuesta de una estrategia de implementación para la producción de bioetanol partiendo de cascarilla de arroz en Colombia (2021)
The main objective of this document is the proposal of a process to obtain bioethanol from rice husk biomass. A review was made of the different existing technologies for the transformation of this raw material into the product of interest, from pretreatment through treatment and fermentation until finally separation and dehydration. Additionally, the physicochemical composition of the Colombian rice husk was analyzed and its potential in the transformation to liquid or solid biofuels. On the other hand, the most appropriate technologies were selected through weighted decision matrices, the result of which indicates that the most appropriate process is composed of a pretreatment with hot liquid water, followed by a treatment with hydrolysis and simultaneous fermentation, to finally use molecular sieves in separation and dehydration of the product. Finally, a description of the operating conditions that can be handled in each of the previously indicated stages was made, it is also accompanied by a mass balance for the production of 30 L of bioethanol and those that can be purchased for the start-up of the process.